Screening performance of different methods defining fetal nasal bone hypoplasia as a single and combined marker for the detection of trisomy 21 in the second trimester. (17th October 2016) - Papasozomenou, Panayiota; Athanasiadis, Apostolos P.; Zafrakas, Menelaos; Panteris, Eleftherios; Mikos, Themistokles; Daniilidis, Angelos; Loufopoulos, Aristoteles; Assimakopoulos, Efstratios; Tarlatzis, Basil C.
Abstract: Objective : To evaluate different methods of defining fetal nasal bone hypoplasia in the second trimester for the detection of trisomy 21. Methods : Prospective study in Greek women undergoing anomaly scan between 18 + 0 and 23 + 6 weeks. The following methods of defining nasal bone hypoplasia were evaluated, either as a single marker or in combination with others: (1) BPD to nasal bone length (NBL) ratio; (2) multiples of the median (MoM) of NBL, according to normal curves from a Greek population; (3–4) NBL < 2.5 percentile according to normal curves (3) commonly used internationally curves and (4) curves from a Greek population. Results : In total, 1301 singleton fetuses were evaluated − 10 with trisomy 21. The best detection rate of trisomy 21 was achieved when the applied method was nasal bone percentiles adjusted to maternal ethnicity, in combination with other markers (<2.5 percentile according to normal curves from a Greek population; p  < 0.001; sensitivity 50%; specificity 94.8%; false-positive rate 5.2%; positive likelihood ratio 9.6). Conclusion : Screening performance of fetal nasal bone hypoplasia in detecting trisomy 21 varies according to the method applied. The best screening performance is achieved by using percentiles adjusted to maternal ethnicity in combination with other markers of aneuploidy.